A predictive model and socioeconomic and demographic determinants of under-five mortality in Sierra Leone. Issue 3 (March 2020) - Tagoe, Eunice Twumwaa; Agbadi, Pascal; Nakua, Emmanuel K.; Duodu, Precious Adade; Nutor, Jerry John; Aheto, Justice Moses K.
Abstract: Sierra Leone is among the countries that recorded high under-five child mortality rate in the world. To design and implement policies that can address this public health challenge, the present study developed a predictive model of factors that explained under-five mortality in Sierra Leone using the 2008 and 2013 Sierra Leone Demographic and Health Survey (SDHS) datasets. LASSO regression technique was used to select the predictors to build the under-five predictive single-level logit and multilevel logit models. Statistical analyses were performed in the R freeware version 3.6.1. About 588 (10.4%) and 1320 (11.1%) children under five were reported dead in 2008 and 2013, respectively. The significant predictors of under-five mortality in Sierra Leone were the total number of children ever born, number of children under five in the household, mother's birth in the last five years, mother's number of living children, and number of household members, household wealth, maternal contraceptive use and intention, number of eligible women in the household, type of toilet facility, sex of the child, and weight of the child at birth. The study identified certain predictors that deserve policy attention and interventions to strengthen the efforts of creating child welfare and survival atmosphere in Sierra Leone. Abstract : Public health; Quality of life; Epidemiology; Pediatrics; Health disparity; Under-five mortality, LASSO Regression, Predictive model, Sierra Leone, Sub-saharan africa